Association of gonadal hormones and sex hormone binding globulin with risk of diabetes: A cohort study in middle‐aged and elderly Chinese males. Issue 5 (21st January 2021) - Li, Na; Huang, Chulin; Lan, Biyun; Lin, Diaozhu; Wang, Chengzhi; You, Lili; Li, Lingling; Li, Fangping; Xiao, Huisheng; Yan, Li; Lao, Guojuan; Sun, Kan
Abstract: Aim: Late‐onset hypogonadism in men is related to the development of diabetes. The association of gonadal hormones, sex hormone binding globulin with diabetes has been studied in various studies. However, there is no cohort study on the relationship between gonadal hormone, sex hormone binding globulin and diabetes in Chinese. We aimed to provide an insight into the possible association in middle‐aged and elderly Chinese males. Methods: We included a population sample of 673 subjects aged 40 years or older. Total testosterone (TT), sex hormone binding globulin (SHBG), follicle‐stimulating hormone (FSH) and luteinising hormone (LH) were detected. The homeostasis model assessment of insulin resistance (HOMA‐IR) was calculated to estimate insulin sensitivity. Diabetes was diagnosed according to the 2010 American Diabetes Association criteria. Results: With an average follow‐up time of 3.2 ± 0.5 years, 9.8% of participants had developed diabetes. The prevalence of diabetes was decreased according to increasing SHBG quartiles (Q1:13.1%, Q2: 12.0%, Q3: 11.2%, Q4: 3.0%, P for trend < .0001) and TT (Q1:16.0%, Q2: 7.9%, Q3: 9.0%, Q4: 6.4%, P for trend < .0001). The ORs of diabetes for increasing SHBG quartiles were 4.52 (95% CI 1.40‐14.57), 4.32 (95% CI 1.33‐14.06), 3.89 (95% CI 1.21‐12.50) and 1.00 (reference) respectively. But the odds of prevalent diabetes were not increased in different quartiles of TT, FSH and LH. In subgroup analyses, the relationship between SHBG and risk of incident diabetes was significantly increased in the population aged over 60, without insulin resistance and with eGFR < 90 mL/min per 1.73 m 2 . Conclusions: Compared with gonadal hormones, a lower level of SHBG is independently associated with the risk of diabetes in middle‐aged and elderly Chinese males.